The Law of Patronage in Early Modern England - O'Day, Rosemary (The journal of ecclesiastical history, 1975)
The calibre of the early Elizabethan clergy left much to be desired and much criticism was levelled by contemporaries and near contemporaries at the bishops for their failure to check the flow of insufficient ministers into benefices. While historians have acknowledged the existence of legal obstacles in the way of a firm episcopal policy in this regard, and have come gradually to realise some of the profound implications of the patronage system, no one has charted in detail the law of patronage which so hampered hierarchical attempts to raise the standard of the parochial clergy.